ANALISIS STRATEGI PROMOSI EDUWISATA DI KABUPATEN JEMBER DALAM MENINGKATKAN JUMLAH PENGUNJUNG PASCA PANDEMI COVID-19 - Lailatul mafazah; Heru baskoro; Diany faila sophia (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2022)
This study aims to identify educational tourism promotion strategies in Jember which were opened by PT X. The educational tourism area was inaugurated in 2016. However, at the beginning of 2020, the outbreak of the Covid-19 pandemic which hit Indonesia caused the tourism industry's visit statistics to decline. and one of the tours that was affected, namely the edutourism area managed by PT X. This resulted in social restrictions/lockdowns and restrictions on tourist visits resulting in a decrease in the number of visitors. Researchers are interested in studying the promotion strategies used for recovery after the Covid-19 pandemic. The research method used was descriptive qualitative analysis, namely the researcher explained the various promotional tools used by PT X. Data collection techniques were carried out through in-depth interviews with data analysis techniques using data triangulation. The results of this study are the promotion strategies used include sales promotion, personal selling, word of mouth, direct marketing. Among the four promotional tools, the most effective is personal selling, where a face-to-face approach is optimal for persuading potential visitors.